Computed tomography in diagnosis and management of aneurysm of the vein of Galen. Issue 9 (September 1979) - Macpherson, P; Teasdale, G M; Lindsay, K W
Abstract : A case of aneurysm of the vein of Galen is presented to demonstrate the value of computed tomography, not only as a diagnostic procedure, but also in the overall management of the condition.